2017
DOI: 10.1016/j.aott.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thoracic vertebrae rotation in patients with pectus excavatum

Abstract: PurposeThe aim of our study was to evaluate thoracic vertebrae rotation in patients with pectus excavatum. Moreover, we wanted to assess the prevalence, the severity and relationship between pectus excavatum and adolescent idiopathic scoliosis (AIS).MethodsWe performed retrospective analysis of 82 preoperative chest CT in children with pectus excavatum performed between January 2008 and December 2011. For each patient Haller Index and Cobb angle was measured. To evaluate the severity of thoracic scoliosis we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…One study was identified by backward citation. Eventually, 48 studies were included: 19 in category I [ 5 , 9 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ], 21 in category II [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , and 8 in category III [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ( Figure 1 ).
Figure 1 PRISMA 2020 flow diagram of identification, screening, and inclusion of papers in the 3 categories.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study was identified by backward citation. Eventually, 48 studies were included: 19 in category I [ 5 , 9 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ], 21 in category II [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , and 8 in category III [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ( Figure 1 ).
Figure 1 PRISMA 2020 flow diagram of identification, screening, and inclusion of papers in the 3 categories.
…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies focused on the association between PD and scoliosis, of which 4 described cases [ 9 , 20 , 24 , 27 ], 5 described spinal change after PD correction [ 19 , 21 , 23 , 25 , 26 ], and 2 PD change after scoliosis correction [ 17 , 28 ]. Thirteen studies analyzed predictive factors [ 5 , 16 , 18 , 19 , [21] , [22] , [23] , 25 , 26 , [29] , [30] , [31] , [32] ], of which three solely included patients with PD-associated scoliosis [ 25 , 29 , 32 ] (Appendix B). Five of these 13 studies did not describe inclusion criteria regarding either scoliosis or syndromic cases [ 16 , 18 , 23 , 25 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Omaník et al [45] and Kokavec and Novorolský [46] report that more than 20% of patients with pectus excavatum also have associated idiopathic scoliosis or spinal kyphoscoliosis. Tomaszewski et al [47] have shown that deformation of the anterior thoracic wall promotes rotation of the thoracic spine. Our study did not show a statistically significant difference in physical activity levels in groups of subjects depending on chest deformity.…”
Section: Health Problems Of Civilizationmentioning
confidence: 99%